When knowledge is an asset: Explaining the organizational structure of large law firms - James B. Rebitzer; Lowell J. Taylor (Levy Economics Institute of Bard College, 2006)
We study the economics of employment relationships through theoretical and empirical analyses of an unusual set of firms, large law firms. Our point of departure is the property rights approach that emphasizes the centrality of ownership's legal rights to control important, nonhuman assets of the enterprise. From this perspective, large law firms are an interesting and potentially important object of study, because the most valuable assets of these firms take the form of knowledgeparticularly knowledge of the needs and interests of clients. We argue that the two most distinctive organizational features of large law firms, the use of up or out promotion contests and the practice of having winners become residual claimants in the firm, emerge naturally in this setting. In addition to explaining otherwise anomalous features of the up-or-out partnership system, this paper suggests a general framework for analyzing organizations where assets reside in the brains of employees.
Keywords: J4; L2; M5; 330; Law firms; property rights; human capital